Disability as a social construct : legislative roots - Liachowitz, Claire H. (Book collections on Project MUSE., 1988)
Wounded soldiers, injured workers, handicapped adults, and physically impaired children have all been affected by legislation that reduces their opportunities to live a functional life. In Disability as a Social Construct, Claire Liachowitz contends that disability is not merely a result of a handicap but can be imposed by society through devaluation and segregation of people who deviate from physical norms. She analyzes pertinent American legislation, primarily from 1770 to 1920, to provide a new perspective on the mechanisms that translate physical defects into social and civil inferiority.